Stem and pseudostem growth play a key role in biomass accumulation of guineagrass in long regrowth cycles - Brunetti, Henrique Bauab; Oliveira, Ricardo Ferraz De; Pezzopane, José Ricardo Macedo; Pedreira, Bruno Carneiro; Carvalho, Rogério Falleiros [UNESP]; Pedreira, Carlos Guilherme Silveira; Santos, Patrícia Menezes (CSIRO Publishing, 2022)
Context: Tall bunch-type tropical forage grasses are known for their rapid (true) stem elongation late in the regrowth cycle, even during the vegetative phase. Aims: This study aimed to evaluate the stem and pseudostem growth pattern of 'Mombaça' guineagrass [Megathyrsus maximus (Jacq.) BK Simon & SWL Jacobs] grown in field conditions and how this relates to its high biomass accumulation during long regrowth cycles. Methods: A guineagrass field was managed from December 2017 to January 2019, in three regrowth cycles of 10, 14 and 12 weeks duration. Individual tillers were assessed weekly to measure stem, pseudostem and leaf elongation, leaf appearance; and angle of insertion of the leaves. Aboveground biomass samples were taken weekly for biomass accumulation and leaf area index assessment. Key results: At the beginning of each regrowth cycle, the pseudostem elongated while the stem length remained constant. Subsequently, the pseudostem length reached a plateau, while the stem length increased at a constant rate. Because of a positive relationship between pseudostem and leaf laminae lengths, the long pseudostem ensured the formation of long leaves in tall tillers and positive net leaf elongation in long regrowth cycles. Conclusions: The high biomass accumulation reflected the continuous positive net leaf elongation by the tillers and was underpinned by the younger leaves being more erect than the older ones, allowing for lower self-shading of the older leaves and greater leaf tissue retention. Implications: The high production of tropical forage grasses in late regrowth should be utilised with caution, as it is underpinned by stem elongation and meristem elevation.
Keywords: C4 forage grasses; internode elongation; leaf appearance rate; Megathyrsus maximus (Jacq.) BK Simon & SWL Jacobs (syn. Panicum maximum Jacq.); pseudostem length; stem elongation; warm-season perennial forage grasses; youngest expanded leaf laminae length